2012
DOI: 10.1002/hbm.22204
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of tractography of the optic radiations

Abstract: Imaging and delineation of the optic radiations (OpR) remains challenging, despite repeated attempts to achieve reliable validated tractography of this complex structure. Previous studies have used varying methods to generate representations of the OpR which differ markedly from one another and, frequently, from the OpR’s known structure. We systematically examined the influence of a key variable that has differed across previous studies, the tractography seed region, in 13 adult participants (9 male; mean age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 44 publications
0
43
0
Order By: Relevance
“…Injury to the posterior part of the optic radiations may cause homonymous inferior quadrantanopia and injury to the central part of the optic radiation fibers may cause macular visual defects. 7,28,124 While the function of the MdLF is still unclear, Makris et al suggested that by connecting the superior temporal gyrus with the angular and superior occipital gyri it plays a role in cognitive functions in the right hemisphere and language in the left hemisphere (Table 2). 61,67,110 A cortical incision that extends into the dominant angular gyrus may also cause Gerstmann syndrome (right-left confusion, digital agnosia, agraphia, and acalculia), and visual memory loss and neglect in the nondominant hemisphere, due to damage of the SLF II and dorsal part of the AF (Tables 2 and 3).…”
Section: 573112mentioning
confidence: 99%
“…Injury to the posterior part of the optic radiations may cause homonymous inferior quadrantanopia and injury to the central part of the optic radiation fibers may cause macular visual defects. 7,28,124 While the function of the MdLF is still unclear, Makris et al suggested that by connecting the superior temporal gyrus with the angular and superior occipital gyri it plays a role in cognitive functions in the right hemisphere and language in the left hemisphere (Table 2). 61,67,110 A cortical incision that extends into the dominant angular gyrus may also cause Gerstmann syndrome (right-left confusion, digital agnosia, agraphia, and acalculia), and visual memory loss and neglect in the nondominant hemisphere, due to damage of the SLF II and dorsal part of the AF (Tables 2 and 3).…”
Section: 573112mentioning
confidence: 99%
“…The drawback of this method was that it relied heavily on manual ROI delineation and individualized parameter tuning, making it difficult to apply to large scale studies. On a sample of 13 subjects, Benjamin et al (2014) studied the manual placement of multiple seed ROIs in white matter around the LGN for the reconstruction of each component of the optic radiation. The final bundle was formed by combining the components, but the typical final product obtained in that study did not form the expected continuous sheet representation of the optic radiation.…”
Section: Introductionmentioning
confidence: 99%
“…The OR is commonly described in three parts, namely the superior, central, and inferior parts, each corresponding to different areas of the visual field (Ebeling and Reulen, 1988). In particular, Meyer’s loop is part of the inferior bundle, which originates from the lateral geniculate nuclei (LGN), propagates anteriorly from the LGN to the temporal lobe, hooks around the inferior horn (IH) of the lateral ventricle (sharp turn) and back projects towards the occipital pole (OP) to form a continuous layer of fibers (Ebeling and Reulen, 1988; Rubino et al, 2005; Benjamin et al, 2014). This fascicle is well understood from conventional Klingler dissection and histological analysis as it has been studied intensively in the past (Ebeling and Reulen, 1988; Ture et al, 2000; Sincoff et al, 2004; Peuskens et al, 2004; Rubino et al, 2005; Choi et al, 2006; Peltier et al, 2006; Pujari et al, 2008; Chowdhury and Khan, 2010), mainly because of it primary function: transmitting visual information.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have attempted to reconstruct the OR using diffusion tensor imaging (DTI) (Yamamoto et al, 2005; Sherbondy et al, 2008b; Yogarajah et al, 2009; Hofer et al, 2010; Clatworthy et al, 2010; Winston et al, 2011; Wu et al, 2012; Tax et al, 2014a; Benjamin et al, 2014; Lilja et al, 2014; Dayan et al, 2015) and high order models based on high angular resolution diffusion imaging (HARDI) acquisitions (Nowell et al, 2015; Martinez-Heras et al, 2015; Kammen et al, 2015; Bernier et al, 2014). The clinical motivation behind most of these studies was to obtain an accurate model of the OR for the preoperative planning in anterior temporal lobe resection surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation